2020
DOI: 10.1155/2020/5989206
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Thai Cajuput Oil and Its Effect on Efflux-Pump Gene Expression in Fluconazole-Resistant Candida albicans Clinical Isolates

Abstract: Candidiasis caused by the fluconazole-resistant opportunistic pathogen Candida albicans is an intractable clinical problem that threatens immunocompromised or normal individuals. The most common mechanism of fluconazole resistance in C. albicans is the failure of cells to accumulate the drug due to increased expression of the efflux proteins encoded by the CDR1, CDR2, and MDR1 genes. Because the number of current antifungal drugs is limited, it is necessary to develop new therapeutic strategies. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The EO of Melaleuca quinquenervia (niaouli oil) was found to be effective against bacteria as well as a range of fungi, including C. albicans [ 22 ]. Additionally, Keereedach et al found that Melaleuca cajuputi (cajeput oil) had potent antifungal activity against clinical isolates of C. albicans resistant to FLC, where it was able to reduce the MIC of FLC and reduce the expression level of MDR1 (an important gene that plays a role in resistance to azole drugs in C. albicans ) [ 23 ]. However, so far, there are few studies regarding the effect of niaouli and cajeput oils in Candida species, with this being the first study to use both oils in Candida biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…The EO of Melaleuca quinquenervia (niaouli oil) was found to be effective against bacteria as well as a range of fungi, including C. albicans [ 22 ]. Additionally, Keereedach et al found that Melaleuca cajuputi (cajeput oil) had potent antifungal activity against clinical isolates of C. albicans resistant to FLC, where it was able to reduce the MIC of FLC and reduce the expression level of MDR1 (an important gene that plays a role in resistance to azole drugs in C. albicans ) [ 23 ]. However, so far, there are few studies regarding the effect of niaouli and cajeput oils in Candida species, with this being the first study to use both oils in Candida biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the tea tree EO was found to increase yeast cell permeability and membrane fluidity and to inhibit the acidification of the medium [ 46 ]. Moreover, Keereedach, Hrimpeng, and Boonbumrung recently demonstrated that the cajeput EO has an antifungal effect on fluconazole-resistant C. albicans isolates [ 47 ]. These investigators showed that the cajeput EO reduced the expression level of the C. albicans MDR1 gene, which encodes the multidrug resistance protein 1 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Keereedach, Hrimpeng, and Boonbumrung recently demonstrated that the cajeput EO has an antifungal effect on fluconazole-resistant C. albicans isolates [ 47 ]. These investigators showed that the cajeput EO reduced the expression level of the C. albicans MDR1 gene, which encodes the multidrug resistance protein 1 [ 47 ]. Of note, the antifungal activity of EOs has been shown to be influenced by several factors, such as the original species, geographic and climatic conditions, the biological and physical–chemical properties of the soil, and storage conditions [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…As fluconazole inhibits the synthesis of ergosterol by inhibiting the 14α-demethylase enzyme that is present in the cell membrane, its action will only occur with its presence in the intracellular environment. Therefore, an inhibition of the efflux pump genes is necessary, which may be the possible targets of the essential oil under study [ 54 ].…”
Section: Discussionmentioning
confidence: 99%